Hubungan Pernikahan Usia Dini dengan Kejadian Kanker Serviks di RSUD Dr. Moewardi - Gayatri, Anindita Ratna; Angelia, Affi; Primadewi, Novi (Nexus Kedokteran Klinik, 2013)
Background:Every year the incidence of cervical cancer is increase and the risk of death from cervical cancer is also increased. One of the risk factor of cervical cancer is a history of early marriage. In Indonesia,there are many womenwho married in early age. The purpose of this study is to detemine whether early marriage may increase the risk of cervical cancer. Methods:This research is a case control based study. The sample consist of 30 cervical cancer patients and 30 normal women with total sample of 60 women. The data was collected from medical record and validated questionnaire. The data was analyzed with multiple logistic regression analysis. Results:There is a statistically significant relationship between early marriage and the incidence of cervical cancer. Women who had history of early marriage have risk to get cervical cancer 8,4 times bigger than women who didnât have history of early marriage (p = 0.002; OR = 8,442). Conclusions:Based on this research women who had history of early marriage have risk to get cervical cancer 8,4 times bigger than women who didnât have history of early marriage. Keywords:Early marriage, cervical cancer.